2010
DOI: 10.1002/chem.201000785
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Mode of Action of a Thymidine‐Based Cisplatin Analogue Breaks Resistance in Cancer Cells

Abstract: Cisplatin analogue complexes with platinum(II) and palladium(II) starting from 3',5'-diamino-3',5'-dideoxy-thymidines were synthesized, both with the D-erythro- and D-threo configurations. Complexes of the general formula [MCl(2)L] were obtained and characterized. NMR spectroscopic measurements and single crystal X-ray structure analysis showed that the metal centers are coordinated to the ligands by the amino groups in 3'- and 5'-positions and not through the thymine moiety. All ligands and complexes showed n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 43 publications
0
5
0
1
Order By: Relevance
“…The effect on TrxR and a second thiol-containing enzyme, namely glutathione reductase (GR), was studied on the isolated enzymes following a published procedure. 32 All compounds show strong inhibitory effects on TrxR (EC 50 (Table 1). 53 The elevated generation of reactive oxygen species (ROS), produced by cellular respiration in mitochondria, indicates an imbalance of normal cell metabolism.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect on TrxR and a second thiol-containing enzyme, namely glutathione reductase (GR), was studied on the isolated enzymes following a published procedure. 32 All compounds show strong inhibitory effects on TrxR (EC 50 (Table 1). 53 The elevated generation of reactive oxygen species (ROS), produced by cellular respiration in mitochondria, indicates an imbalance of normal cell metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…S6, ESI †). 50 Consequently, it can be concluded that apoptotic cell death pathways play an important role in the mode of action of these gold peptide conjugates. A highly important regulatory cellular function such as apoptosis can be triggered by a multitude of events and connected signalling pathways.…”
Section: Resultsmentioning
confidence: 99%
“…However, WQF 044 did not break the over-expression of Bcl-2 by 30-fold, existing in the MelHO/Bcl-2 cells, in a dose-dependent manner (Fig. 4 b) (Onambele 2010 ). Another interesting observation was the fivefold over-expression of BAX in the PCR array analysis (Table 2 ).…”
Section: Discussionmentioning
confidence: 92%
“…The intrinsic pathway is associated with the loss of the mitochondrial membrane potential and associated changes in its permeability. , Furthermore, caspase-9 participates as an initiator and caspase-3 as another key component in the mitochondrial pathway. , Western blot analysis after incubating BJAB cells with 5 and 8 nM 7 for 36 h revealed activation of caspase-9 (C9) but no significant activation of caspase-3 (C3) (Figure A). This indicates the involvement of the intrinsic pathway in the induction of apoptosis by 7 as reflected by the appearance of cleaved C9 and small consumption of procaspase-3.…”
Section: Resultsmentioning
confidence: 99%